Mediação nas serventias extrajudiciais: entraves do provimento n. 149/2023 do Conselho Nacional de Justiça ao acesso à justiça multiportas - Trevizan, Rosana Ferreira (2024)
Extrajudicial offices are spaces for citizenship and constitute a potentially adequate means of ensuring the fundamental right of access to justice. In light of these attributes, in 2018, the National Council of Justice (CNJ) published Provision No. 67, later incorporated by the National Code of Extrajudicial Standards (Provision No. 149/2023 of the CNJ), providing for mediation and conciliation within the scope of notary and registry services in Brazil. However, there has been no actual adherence of the offices to these services. In view of this finding, the research aimed to investigate the possible flaws contained in Provision No. 149/2023 of the CNJ that may hinder the application of mediation within the scope of extrajudicial offices and, from there, present mitigation measures so that such services are provided in a more efficient, timely and adequate manner, with a potential contribution to the realization of the fundamental right of access to justice in Brazil. Although the delegates of these services may perform both mediation and conciliation functions, this research was limited, for didactic reasons, to mediation. It is important to note that the research carried out adheres to the area of ​​concentration of the doctoral program, "Fundamental Rights and Guarantees", in the research line "democracy, citizenship and fundamental rights". To this end, the hypothetical-deductive approach method was used, since, based on the flaws in Provision No. 149/2023 of the CNJ, it is possible to outline hypotheses that were tested. Regarding the bibliographic research, it was based on the theoretical frameworks of access to justice - Mauro Cappelletti and Bryan Garth; mediation - Luis Alberto Warat; and the Multi-Door Court - Frank Sander. In addition, documentary research was carried out, of an exemplary nature, to show data on the crisis in the judiciary and data on the dejudicialization promoted by extrajudicial offices. Thus, the yearbooks “Justice in Numbers 2023” and “Notary Offices in Numbers 2022” were used. To carry out the tests, a field survey was conducted – semi-open questionnaire –, through intentional non-probabilistic sampling with delegates of extrajudicial offices and a comparative study between the requirements of the provision and the law. The result of the survey confirmed that Provision No. 149/2023 meets several assumptions established in Law 13.140/2015 – Mediation Law and, through the data from the field survey, it was possible to identify 10 obstacles that confirmed the hypotheses outlined. Finally, a normative proposal was made so that such obstacles can be alleviated and, consequently, that extrajudicial offices may have an interest in developing such a function and, thus, be seen by the population as a route or gateway to access justice within a broad multi-door system